2006
DOI: 10.1111/j.1468-2397.2006.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment processes in social work with children at risk in Sweden and Croatia

Abstract: The aim of this article is to compare Swedish and Croatian social workers’ assessments and protection of a 4‐year‐old child exposed to risk in its own family. The data were collected from 87 Croatian and 72 Swedish social workers by means of a questionnaire, which incorporated a vertical vignette. Effects of the participant's country of residence were investigated with respect to: (i) risk assessments; (ii) perception of the main problems; (iii) tolerance of corporal punishment; (iv) judgements about appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…This study indicated that the same case vignettes were judged differently by practitioners from the two countries, to a large extent reflecting historical developments in public attitudes regarding the costs and benefits of removing children from home . In another study, Brunnberg and Pećnik (2007) found that Croatian social workers were more likely than their Swedish peers to assess a situation as requiring child protection and to favor removal, but no differences were found in judgments about the action needed in response to second-hand information in a case of child maltreatment. Gilbert, Parton and Skivenes (2011) show that some of the between-countries differences reflect the variations in their welfare regimes.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This study indicated that the same case vignettes were judged differently by practitioners from the two countries, to a large extent reflecting historical developments in public attitudes regarding the costs and benefits of removing children from home . In another study, Brunnberg and Pećnik (2007) found that Croatian social workers were more likely than their Swedish peers to assess a situation as requiring child protection and to favor removal, but no differences were found in judgments about the action needed in response to second-hand information in a case of child maltreatment. Gilbert, Parton and Skivenes (2011) show that some of the between-countries differences reflect the variations in their welfare regimes.…”
mentioning
confidence: 94%
“…Findings show that younger, less experienced, and childless workers, and those with a childhood history of corporal punishment or abuse, generally perceive higher risk and are more likely to recommend placing the child in care (Brunnberg & Pećnik, 2007), while more experienced workers are less prone to implement removal recommendations (Arad-Davidson et al, 2003). Other findings show that workers who experienced previous traumas were less likely to assess a child as being at risk (Regehr, LeBlanc, Shlonsky, & Bogo, 2010) and that white and more educated workers were more inclined than others to classify physical injuries as abuse rather than corporal discipline (Jent et al, 2011).…”
mentioning
confidence: 99%
“…Therefore, there was a different assessment perspective about corporal punishment between social workers in the two countries. Brunnberg and Pećnik () reported that Swedish and Croatian social workers responded similarly to the Korean social workers for stage 2 of this vignette.…”
Section: Discussionmentioning
confidence: 81%
“…This result suggests that American social workers consider removal of a child from the home as a last resort, while Korean social workers seem to rely on removal of a child as a default. In a previous study using the same vignette, social workers in both Sweden and Croatia also considered removal of a child a last resort (Brunnberg & Pećnik, ). Both the survey and interview responses indicated that Korean social workers considered the removal of the child as a main safety measure.…”
Section: Discussionmentioning
confidence: 99%
“…These more 'distal' predictors have a relatively smaller contribution to the explanation of intended interventions than the more 'proximal' predictors such as case-characteristics and professionals' reactions to the case (Pecnik & Brunnberg, 2005). The wider context of the social welfare system and culture influences social workers' assessments and recommended interventions to a child abuse case vignette (Gold et al, 2001;Brunnberg & Pecnik, 2007). The role of individual characteristics of the professional worker in determining professional judgements in the field has also been examined, including their socio-demographic characteristics (Portwood, 1998;Rossi et al, 1999), professional experience (Portwood, 1998;Gold et al, 2001) and personal victimization history (Pecnik & Brunnberg, 2005).…”
Section: Professionals' Judgements In Child Protectionmentioning
confidence: 99%